Plasma Surface Modification of 3Y-TZP at Low and Atmospheric Pressures with Different Treatment Times - Kang, Sung Un; Kim, Chul Ho; You, Sanghyun; Lee, Da Young; Kim, Yu Kwon; Kim, Seung Joo; Kim, Chang Koo; Kim, Hee Kyung (International Journal of Molecular Sciences, 2023)
The efficiency of plasma surface modifications depends on the operating conditions. This study investigated the effect of chamber pressure and plasma exposure time on the surface properties of 3Y-TZP with N2/Ar gas. Plate-shaped zirconia specimens were randomly divided into two categories: vacuum plasma and atmospheric plasma. Each group was subdivided into five subgroups according to the treatment time: 1, 5, 10, 15, and 20 min. Following the plasma treatments, we characterized the surface properties, including wettability, chemical composition, crystal structure, surface morphology, and zeta potential. These were analyzed through various techniques, such as contact angle measurement, XPS, XRD, SEM, FIB, CLSM, and electrokinetic measurements. The atmospheric plasma treatments increased zirconia’s electron donation ((Formula presented.)) capacity, while the vacuum plasma treatments decreased (Formula presented.) parameter with increasing times. The highest concentration of the basic hydroxyl OH(b) groups was identified after a 5 min exposure to atmospheric plasmas. With longer exposure times, the vacuum plasmas induce electrical damage. Both plasma systems increased the zeta potential of 3Y-TZP, showing positive values in a vacuum. In the atmosphere, the zeta potential rapidly increased after 1 min. Atmospheric plasma treatments would be beneficial for the adsorption of oxygen and nitrogen from ambient air and the generation of various active species on the zirconia surface.
Keywords: Atmospheric Pressure; Ceramics; Materials Testing; Surface Properties; Wettability; Yttrium; Zirconium; atmospheric pressure; plasma gases; surface properties; vacuum; zirconium oxide